Does E-governance improve transparency? A case study of South Africa - Kopane, Tebogo (My University, 2019)
The purpose of this research paper is to investigate on whether the presence of e-governance improves transparency in a state. The research report will do so through answering questions posed in the process of investigation which are; How does Information and Communications Technology (ICT) act as a tool of transparency? Are the e-initiatives implemented by the South African government proof that e-governance can improve transparency? These questions are integral in investigating the overarching question “does e-governance improve the presence of transparency?” The research report will embark on a qualitative study, using process tracing as a method of investigation as the primary and secondary resources stem from policy documents, research papers as well as international indices. The research report will use South Africa as a case study from the time period of 1994 since its democratic inception South Africa has been in the forefront of implementing policies that would propel the use of e-governance in ensuring good governance practices. The research report has analysed the implementation of the Thusong Service Centres, National e-health, e-filing as well as e-education.
A research report submitted to the Faculty of Humanities, University of the Witwatersrand, Johannesburg, in partial fulfilment of the requirements for the degree of Master of Arts in International Relations, 2019
Keywords: Corporate governance--South Africa